Different Enrichment Patterns of Magnetic Particles Modulated by Primary Iron‐Phosphorous Input. Issue 22 (13th November 2020) - Ren, Juan; Long, Xiaoyong; Ji, Junfeng; Barrón, Vidal; Torrent, José; Wang, Yong; Xie, Shiyou
Abstract: Magnetic particles associated with iron (Fe) oxides are widespread on the surface of Earth and Mars and serve as reasonable climatic indicators. Ferrimagnetic maghemite (Mgh) and antiferromagnetic hematite (Hm), which dominate magnetism and redness, often coexist or compete with each other in soils and sediments. The formation efficiency of Mgh relative to Hm could be modulated by geochemical background besides climate, especially by phosphate (P), which has a high affinity for the surfaces of precursor iron oxides in natural systems. We investigated two Ferralsol sequences around a P mining field with similar climates and contrasting P/Fe ratios. High P/Fe ratios retard iron oxide crystallization, grain growth, and transformation into Hm, thereby promoting more effective accumulation of ferrimagnetic Mgh as an intermediate product. The lack of ligand‐protected effects well interprets asynchronous changes in magnetism and redness in soils and sediments across large spatiotemporal scales, especially in highly weathered soils. Plain Language Summary: Iron oxides are critical carriers of magnetism and dyeing agents of soils and sediments. The concentration of pedogenic maghemite (Mgh) and hematite (Hm), which dominate magnetism and redness, is considered to be controlled by the primary iron input and climate conditions. However, phosphate exhibits a high affinity for the surfaces of precursor iron oxides, especially in highly weathered soils. We investigated two Ferralsol sequences around a P mining field with contrasting P/Fe ratios but similar climates. High P/Fe ratios are observed to impede iron oxide crystallization, grain growth, and transformation into Hm, thereby promoting more effective accumulation of ferrimagnetic Mgh as an intermediate product. The presence and absence of ligand‐protected effects help explain asynchronous changes in magnetism and color in nature systems across large spatiotemporal scales. Key Points: Iron oxide crystallinity increases monotonically as soil P/Fe decreases Ferrimagnets accompanying the formation of hematite are enriched with accelerations under high P/Fe but with even rates under low P/Fe Ferrimagnets grow and transform into hematite more rapidly without the proper level of P ligand protection